The status of California yellowtail Seriola dorsalis as a commercially ready species for marine U.S. aquaculture. Issue 3 (15th June 2021) - Rotman, Federico; Stuart, Kevin; Silbernagel, Constance; Drawbridge, Mark
Abstract: California yellowtail (CYT; Seriola dorsalis ) is a promising candidate for marine aquaculture in the United States because there is an existing market and cultured Seriola spp. command prices as high as 27.70 per kg for head‐on gutted product. Methods for commercial‐scale Seriola spp. fingerling production and growout have been refined globally in recent years. Spawning can be accomplished without hormone therapy and adults spawn viable eggs when ambient water temperatures are between 15 and 22°C. Larval culture of CYT includes rotifers and Artemia, with the addition of greenwater. Larval survival to 1 g juveniles (45 days post hatch) is typically high at 30–60%. However, poor swim bladder inflation and skeletal malformations require culling and can reduce this yield substantially. Growout of CYT to market size at Hubbs‐SeaWorld Research Institute (HSWRI) has been completed on a very limited basis in flow through tanks where it takes 18–24 months to achieve a market weight of 3.5–4.0 kg. While culture of this species is commercially ready from a technical and business perspective, research is still needed to improve swim bladder inflation, reduce deformities, optimize nutrition across all life stages, and assist with disease diagnosis and control. Most notable among bottlenecks to commercialization in the United States is the need for growout capacity both for net pen and land‐based culture.